Communication practice in village data collection - Pitaloka, Rieke Diah; Hendriyani, Hendriyani; Eriyanto, Eriyanto; Haryatmoko, Haryatmoko (Faculty of Communications Science, Dr. Soetomo University, 2022)
This study analyses two communication practices for rural data collection in Indonesia: top-down, carried out by the state, and bottom-up, initiated by collective intellectuals. This research is to reveal how to communicate rural data collection actions. The differences in data manifest the practice of communicating rural data collection actions; and Doxa, habitus, and symbolic violence that is ‘hidden’ in the procedures and mechanisms of data collection run by the state. The study area is Tegallalang Village, Gianyar Regency, Bali. Quantitative data in Prodeskel from the Ministry of Home Affairs and Precision Village Data (DDP) with a Drone Participatory Mapping approach were obtained independently by researchers. The research used Mixed Methods Research. Qualitative data were obtained through in-depth interviews using the Nvivo R1 application analysis. Knife analysis using Pierre Bourdieu and Nick Couldry. The study results found two differences in the practice of rural data collection, namely; first, the difference in data collection actors. The state represents Prodeskel, and collective intellectuals represent DDP; second, the difference in data is due to differences in the practice of communication actions (procedures and mechanisms) of data collection. Prodeskel data with a top-down approach produces low-accuracy data and vice versa for DDP. This research also reveals the opus operatum of communication actions in the form of Doxa, habitus, and symbolic violence in data collection of the country’s countryside and digital technology to build a space for communication and citizen participation which is the key to the birth of DDP.